2017
DOI: 10.1186/s12913-016-1963-8
|View full text |Cite
|
Sign up to set email alerts
|

The integrated care pathway for post stroke patients (iCaPPS): a shared care approach between stakeholders in areas with limited access to specialist stroke care services

Abstract: BackgroundLack of intersectoral collaboration within public health sectors compound efforts to promote effective multidisciplinary post stroke care after discharge following acute phase. A coordinated, primary care-led care pathway to manage post stroke patients residing at home in the community was designed by an expert panel of specialist stroke care providers to help overcome fragmented post stroke care in areas where access is limited or lacking.MethodsExpert panel discussions comprising Family Medicine Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 23 publications
(22 reference statements)
0
26
0
1
Order By: Relevance
“…Besides that, approximately 90% of stroke survivors have functional sequelae (2) , and only 5% to 20% of patients achieve full functional recovery (3) . A stroke is not only one of the most common disease today but also a global public health concern in terms of mortality, disability, and demand for medical and social overheads (4,5) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides that, approximately 90% of stroke survivors have functional sequelae (2) , and only 5% to 20% of patients achieve full functional recovery (3) . A stroke is not only one of the most common disease today but also a global public health concern in terms of mortality, disability, and demand for medical and social overheads (4,5) .…”
Section: Introductionmentioning
confidence: 99%
“…However, studies around the world show that the ongoing patient care in the community is far from ideal, highlighting the variations in the delivery of health services, unmet needs of specialties, and the lack of long-term care guidelines (13,5) . Moreover, these studies highlight that there is a sharing of knowledge and ongoing care between hospital and community teams when related to chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stroke significantly impacts the physical functioning of survivors. Studies have shown that between 35% and 80% of stroke survivors exhibit certain forms of physical dysfunction following the onset of acute stroke [5,6]. Among the survivors measured at later stage post-stroke, more than half have difficulty in walking, and nearly one-fifth were dependent on others for activities in daily living [5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that between 35% and 80% of stroke survivors exhibit certain forms of physical dysfunction following the onset of acute stroke [5,6]. Among the survivors measured at later stage post-stroke, more than half have difficulty in walking, and nearly one-fifth were dependent on others for activities in daily living [5,6,7]. These physical dysfunctions are often associated with the presence of post-stroke impairments, resulting in an increased energy demand and oxygen consumption to perform simple day-to-day tasks.…”
Section: Introductionmentioning
confidence: 99%